A lower dosage of imatinib in patients with gastrointestinal stromal tumors with toxicity of the treatment. Issue 49 (December 2016) - Yin, Yuan; Xiang, Jin; Tang, Sumin; Chen, Jiaju; Yu, Qin; Zhang, Bo
Abstract : Abstract: This study investigated the efficiency and safety of imatinib in the lower dose (300 mg/d) in patients with gastrointestinal stromal tumor (GIST) who cannot tolerate imatinib in the standard dose (400 mg/d). Steady-state imatinib trough concentration (Cmin) values in 18 patients with GIST who were taking 300 mg/d or 400 mg/d imatinib were measured. The clinical features, toxicity data, and follow-up data were collected. Around 18 patients with GIST were investigated in which 9 patients received 300 mg/d imatinib. The mean imatinib Cmin value of the 18 patients was 1841 ng/mL (1018–3897 ng/mL). The difference between the patients treated with 400 mg/d (n=9) and those treated with 300 mg/d (n = 9), which have imatinib Cmin values of 2122±1003 ng/mL and 1559±478 ng/mL, respectively, was not significant ( P = 0.148). In total, 12 of the 18 patients had complete resection of the primary tumor, 8 of whom received postoperative imatinib 300 mg/d. After the average follow-up of 15.4 months, no recurrence was documented. Of the 6 patients with unresected GIST, 1 received imatinib 300 mg/d for 13 months. The tumor size of this patient continued to decrease. In contrast to patients treated with imatinib 400 mg/d, patients treated with imatinib 300 mg/d notably exhibited lesser drug-related side effects. Patients with GIST who exhibited intolerance to the standard dose of imatinib (400 mg/d), a lower dose of 300 mg/d could provide not only sufficient plasma Cmin and good disease control but also the alleviation of the side effects.